(untitled) (Journal of Information Systems and Technology Management, 2009)
Communication technologies have a renovating role in contemporaneity with regard to human interaction. One can however highlight their influence on other everyday aspects, like their influence in research. The objective of this paper is to describe and discuss the aspects that involve the application of focal groups in a virtual environment, denominated on-line focal groups, with the aim of highlighting factors that can guide their use in research, especially for research which is geared towards investigating opinions and perceptions of social players. The aspects broached in this paper are based in part on the application experience of the players, with a view to elaborating a doctorate thesis. The theoretical fundamentals of presential focal groups and their migration to the virtual environment are also broached. Finally some suggestions are presented to those who are interested in this research strategy, based on the results obtained through this experience..